Women and the Catholic Church Negotiating Identity and Agency - McEwan, Tracy; McEwan, Tracy (London Bloomsbury Academic Bloomsbury Academic [Imprint], 2025)
How do Catholic women make sense of their involvement in a church with restrictive gendered roles and responsibilities? Is there a vision for church which might provide Catholic women with a community of hope, justice and flourishing? Introducing a new methodological approach to studying Catholic women, this open access book provides fresh insights into women’s religious and spiritual experiences and church participation. Drawing on a case study of Australian Catholic women, Tracy McEwan develops the notion of “technologies of Catholicism” to explore the ways in which women shape their religious and secular identities against the backdrop of a masculinist Church. This book is a key resource for those seeking to understand women’s struggle to negotiate the impact of Catholicism and its oppressive gendered theologies. It introduces the term “everyday spiritual abuse” to explain the harm Catholic women experience on a day-to-day basis as they negotiate multiple material, spiritual, and structural inequalities. It proposes an alternative feminist model of church, which is contained and produced in the herstories of women. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the Bloomsbury Open Collections Library Collective
Anmerkungen zur Barrierefreiheit: Accessibility options of PDF file not available.
eng
Keywords: Society and Social Sciences; Society and culture: general; Social and ethical issues; Violence and abuse in society; Domestic abuse; Philosophy and Religion; Religion and beliefs; Christianity; Christian Churches, denominations, groups; Roman Catholicism, Roman Catholic Church